Low-Dose Mycophenolate Mofetil for Treatment of Neuromyelitis Optica Spectrum Disorders: A Prospective Multicenter Study in South China - Huang, Qiao; Wang, Jingqi; Zhou, Yifan; Yang, Hui; Wang, Zhanhang; Yan, Zhenwen; Long, Youming; Yin, Jia; Feng, Huiyu; Li, Caixia; Lu, Zhengqi; Hu, Xueqiang; et al. (Frontiers in Immunology, 2018)
Objective To evaluate the efficacy and safety of low-dose mycophenolate mofetil (MMF，1000 mg/day) treatment of neuromyelitis optica spectrum disorders (NMOSDs). Methods This study was a multicenter, open, prospective, follow-up clinical trial. The data include retrospective clinical data from the pretreatment phase and prospective data from the posttreatment phase. From September 2014 to February 2017, NMOSD patients seropositive for aquaporin 4-IgG (AQP4-IgG) were treated with low-dose MMF. Results Ninety NMOSD patients were treated with MMF for a median duration of 18 months (range 6-40 months). The median annual recurrence rate (ARR) decreased from 1.02 before treatment to 0 (P<0.0001) after treatment, and the Expanded Disability Status Scale (EDSS) score decreased from 4 to 3 (P<0.0001). The EDSS score was significantly lower (P=0.038) after the first 90 days of treatment. The serum AQP4-IgG titer decreased in 50 cases (63%). The median Simple McGill pain score (SF-MPQ) was reduced in 65 patients (88%) with myelitis from 17 (range 0-35) to 11 (range 0-34) after treatment (P<0.0001). The median Hauser walking index (Hauser Walk Rating Scale) was reduced from 2 (range 1-9) before treatment to 1 (range 0-7) after treatment (P<0.0001). Adverse events were documented in 43% of the patients, and eight patients discontinued MMF due to intolerable adverse events. Fourteen (16%) of the total patients discontinued MMF after our last follow-up for various reasons and switched to azathioprine or rituximab. Conclusion Low-dose MMF reduced clinical relapse and disability in NMOSD patients in South China. However, some patients still suffered from adverse events at this dosage.